RVFV virulence factor NSs triggers the mitochondrial MCL-1-BAK axis to activate pathogenic NLRP3 pyroptosis. - Zhenqiong Guan; Huiling Li; Chongtao Zhang; Ziyan Huang; Meidi Ye; Yulan Zhang; Shufen Li; Ke Peng (PLoS Pathogens)
Infection of Rift Valley fever virus (RVFV), a highly pathogenic mosquito-borne zoonotic virus, triggers severe inflammatory pathogenesis but the underlying mechanism of inflammation activation is currently unclear. Here, we report that the non-structural protein NSs of RVFV triggers mitochondrial damage to activate the NLRP3 inflammasome leading to viral pathogenesis in vivo. It is found that the host transcription inhibition effect of NSs causes rapid down-regulation of myeloid cell leukemia-1(MCL-1), a pro-survival member of the Bcl-2 (B-cell lymphoma protein 2) protein family. MCL-1 down-regulation led to BAK activation in the mitochondria, which triggered mtROS production and release of oxidized mitochondrial DNA (ox-mtDNA) into the cytosol. Cytosolic ox-mtDNA binds and activates the NLRP3 inflammasome triggering NLRP3-GSDMD pyroptosis in RVFV infected cells. A NSs mutant virus (RVFV-NSsRM) that is compromised in inducing transcription inhibition did not trigger MCL-1 down-regulation nor NLRP3-GSDMD pyroptosis. RVFV infection of the Nlrp3-/- mouse model demonstrated that the RVFV-triggered NLRP3 pyroptosis contributed to RVFV inflammatory pathogenesis and fatal infection in vivo. Infection with the RVFV-NSsRM mutant virus similarly showed alleviated inflammatory pathogenesis and reduced fatality rate. Taken together, these results revealed a mechanism by which a virulence factor activates the mitochondrial MCL-1-BAK axis through inducing host transcription inhibition to trigger NLRP3-dependent inflammatory pathogenesis.